Protection of Women in Cases of Gender-Based Violence in the Social Community - Nanik Mandasari; Mario Dirgantara; Oktir Nebi; Dodi Alvayed (CV. Abhinaya Indo Group, 2025)
This study aims to analyze the protection of women who are victims of gender-based violence in Yogyakarta. Although there is a legal basis that supports the protection of women through Law Number 23 of 2004 concerning the Elimination of Domestic Violence and Law Number 35 of 2014 concerning Child Protection, the implementation of this policy still faces various challenges, both in terms of social, cultural, and structural aspects. This study uses a descriptive qualitative method with an in-depth interview approach with law enforcement officials, women activists, and victims of violence to explore their understanding and experiences related to this policy. The results of the study show that despite significant efforts from government and non-governmental institutions, strong patriarchal cultural factors in Yogyakarta society discourage victims from reporting, while low levels of legal education leave many women unaware of their rights. In addition, limited human resources and funds to support related institutions are also obstacles in handling cases of gender-based violence. This study concludes that although legal policies have been implemented, improvements in terms of socialization, legal education, and strengthening inter-agency coordination are needed so that legal protection policies can run effectively and provide optimal protection for women victims of gender-based violence in Yogyakarta.